Cryopreservation Effect on Chromogranin A Expression in Neonatal Pig Adrenal Cell Culture - Novikova, Oksana Yu.; Sidorenko, Olga S.; Bozhok, Galina A.; Bondarenko, Tatyana P. (Problems of Cryobiology and Cryomedicine, 2019)
The expression of chromogranin A (CgA) in chromaï¬ƒn cells of adrenal glands of newborn piglets after cryopreservation was studied. Adrenal tissue fragments were cryopreserved using 10% dimethyl sulfoxide and a controlled cooling rate of 1 deg / min down to â€“80Â°Ð¡ with further immersion into liquid nitrogen. Unfrozen fragments were used as an intact control. The cell suspension was obtained by enzymatic method from the fragments, placed into culturing conditions. Cell cultures from intact and cryopreserved fragments represented a monolayer with multicellular spheroids (MS) attached to it. Flow cytometry using antibodies to CgA revealed that the number of CgA-positive cells in cryopreserved samples did not signiï¬cantly diï¬€er from the control ((31.1 Â± 2.7) and (32.9 Â± 3.6)%, respectively). By the immunocytochemical method, in both cultures, on the initial day of culturing the CgA-positive cells were found both in the monolayer and in MS. During culturing the number of these cells did not signiï¬ cantly diï¬€er, however, they were redistributed, i. e. their content in the monolayer decreased and it was increased in the MS. Similar relative numbers of cells with the CgA expression and their distribution nature in both cultures indicated that the cryopreservation of adrenal fragments in the mode used retained the basic structural and functional properties of chromaï¬ƒn cells. Â  Probl Cryobiol Cryomed 2019; 29(4):Â 344-353